Translating asymmetry, rewriting power - Carbonell i Cortés, Ovidi, 1966-; Monzó Nebot, Esther (Benjamins translation library ;, 2021)
"The relevance of translation has never been greater. The challenges of the 21st century are truly glocal and societies are required to manage diversities like never before. Cultural and linguistic diversities cut across ideological systems, those carefully crafted to uphold prevailing hierarchies of power, making asymmetries inescapable. Translation Studies have left behind neutrality and have put forward challenging new approaches that provide a starting point for researching translation as a cultural and historical product in a global and asymmetrical world. This book addresses issues arising from the power vested in and arrogated by translation and interpreting either as instruments of change, or as tools to sustain dominant structures. It presents new perspectives and cutting-edge research findings on how asymmetries are fashioned, woven, upheld, experienced, confronted, resisted, and rewritten through and in translation. This volume is useful for scholars looking for tools to raise awareness as to the challenges posed by the pervasiveness of power relations in mediated communication. It will further help practitioners understand how asymmetries shape their experiences when translating and interpreting"--